RESEARCH OF INNOVATIVE MODELS OF LEARNING IN HIGHER EDUCATION - Kozak, Liudmyla V. (Educological discourse, 2014)
In the article essence and features of the innovative teaching, his influence, is exposed on development of innovative personality of future specialist, the innovative models of teaching are analysed, the innovative going is considered near organization of educational process at higher school, the variability and personality-oriented orientation of the innovative teaching is grounded, positive influence of experience of innovative activity of teachers is well-proven on efficiency of educational process at higher school.